MASA DEPAN PARTAI POLITIK ISLAM DALAM PERTARUNGAN PEMILU 2009 - Yedi Purwanto (Jurnal Sosioteknologi, 2009)
As the majority in this country, the Moslems have an important role in determining who and what party will win the upcoming general election this year and then lead this country for the next five years. Dealing with leadership, Moslems believe that Prophet Muhammad is the best leader ever in the world. However, some Moslem intellectuals argued that Prophet Muhammad was only a religious leader, instead of a political leader. This article discusses any issues on the leadership of Prophet Muhammad that is presumably related to our present national concern, the general election.